Functionalized graphene supported metal monatomic composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611022359.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-10
AI Technical Summary
然而,传统微米或亚微米级前驱体颗粒因扩散路径长、熔融温度高,在热解过程中易发生局部聚集,难以实现原子级分散;同时,其在水相中与带负电的氧化石墨烯之间存在强静电排斥,导致复合不充分,进一步限制单原子形成效率
本发明提供的功能化石墨烯负载金属单原子复合材料,通过特定的方法将金属硫化物纳米颗粒均匀锚定于功能化石墨烯表面,并经低温热解原位转化为高密度、高分散的金属单原子位点,显著提升了材料的界面活性与结构稳定性。该复合材料中,功能化石墨烯不仅提供高导电网络和丰富缺陷锚定位点,其表面含氧官能团还可有效捕获并稳定金属单原子,防止其在电化学循环或热处理过程中迁移团聚。
Smart Images

Figure CN122532218B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst preparation, and more specifically, to a functionalized graphene-supported metal nitrogen atom composite material, its preparation method, and its application. Background Technology
[0002] In recent years, single-atom catalysts (SACs) have become a research hotspot in energy conversion, environmental remediation, and electrochemical energy storage due to their near 100% atom utilization, unique electronic structure, and excellent catalytic selectivity. In SACs, the metal active centers are anchored to the support surface as isolated single atoms, and their performance is highly dependent on the chemical composition, defect structure, and surface functional group distribution of the support. Therefore, developing ideal supports that combine high specific surface area, abundant anchoring sites, and good conductivity is key to the controllable preparation of high-performance single-atom materials.
[0003] Graphene and its derivatives (such as graphene oxide, GO) are widely used as support platforms for single-atom catalysts due to their two-dimensional topology, high specific surface area, excellent electron transport capabilities, and abundant oxygen-containing functional groups (such as carboxyl, hydroxyl, and epoxy groups). These oxygen-containing groups can not only serve as coordination sites for metal precursors, but also form topological defects (such as vacancies and edge sites) through deoxidation during heat treatment, further stabilizing metal single atoms and preventing their migration and aggregation.
[0004] However, the preparation of graphene-based single-atom materials in existing technologies still faces several challenges. First, traditional methods often employ strong acid / base treatment or high-temperature reduction to functionalize graphene, which can easily lead to structural damage or excessive removal of functional groups, thus reducing the number of effective single-atom anchoring sites. Second, the loading process of metal precursors (such as metal salts or organic complexes) on the graphene surface often lacks spatial confinement effects, making it difficult to achieve a high-density, uniformly dispersed single-atom distribution, which is prone to aggregation and formation of nanoparticles during subsequent pyrolysis. Third, although introducing additional heteroatoms (such as N, S, P) to introduce anchoring sites can improve single-atom stability, the doping process is complex and costly, and may introduce uncontrollable defects, affecting the intrinsic conductivity of the material.
[0005] To overcome these problems, researchers attempted a "precursor sacrifice method," which involves first combining metal sulfides (or other relatively low-melting-point metal compounds) with graphene, then decomposing them through high-temperature pyrolysis to release metal atoms that are captured by defects in the graphene. However, traditional micron or submicron-sized precursor particles are prone to local aggregation during pyrolysis due to their long diffusion paths and high melting temperatures, making atomic-level dispersion difficult. Furthermore, strong electrostatic repulsion exists between them and negatively charged graphene oxide in the aqueous phase, leading to insufficient recombination and further limiting the single-atom formation efficiency. Summary of the Invention
[0006] Based on the aforementioned technical problems in the existing technology, the present invention provides a method for preparing functionalized graphene-supported metal single-atom composite materials. This method can efficiently prepare functionalized graphene-supported metal single-atom composite materials with a large loading capacity. When used as an electrode active material in batteries, it can exhibit high discharge specific capacity at high current densities and excellent cycle performance.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows: A method for preparing a functionalized graphene-supported metal single-atom composite material includes the following steps: S1. Disperse the metal sulfide and graphene oxide evenly in water to obtain sulfide suspension and graphene oxide suspension respectively. S2. Mix the sulfide suspension and the graphene oxide suspension evenly to obtain a mixed suspension; S3. Add the weak electrolyte salt to the mixed suspension, mix evenly, and then heat to carry out the reaction. After the reaction is completed, dry the product to obtain precursor particles. S4. Place the precursor particles in a protective atmosphere or vacuum, and heat them for sintering to obtain a functionalized graphene-supported metal single-atom composite material. The metal sulfide is a sulfide of at least one of Mg, Ni, Co, Fe, Sb, and Pt.
[0008] In some embodiments, in step S1, the concentration of the sulfide suspension is 0.05-0.5 g / mL; and the concentration of the graphene oxide suspension is 0.1-20 mg / mL.
[0009] In some embodiments, in step S2, the volume ratio of the sulfide suspension to the graphene oxide suspension is (0.05-5):1.
[0010] In some embodiments, the reaction temperature in step S3 is 50-90°C.
[0011] In some implementations, the reaction time in step S3 is 20-240 min.
[0012] In some embodiments, in step S3, the mass of the weak electrolyte salt is 0.05-0.5 of the mass of the mixed suspension.
[0013] In some embodiments, in step S3, the addition rate of the weak electrolyte salt is indicated by the complete dissolution of the weak electrolyte salt; that is, the weak electrolyte salt is added to the mixed suspension in batches, with the next batch added only after the previous batch has completely dissolved, and the addition is completed in 10-30 minutes.
[0014] In some embodiments, in step S3, after the reaction is complete, the solid and liquid are separated, and the solid is freeze-dried to obtain a functionalized graphene-supported sulfide nanoparticle precursor.
[0015] In some embodiments, in step S3, the weak electrolyte salt includes at least one of ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, ammonium carbonate, sodium carbonate, and potassium carbonate.
[0016] In some embodiments, the sintering temperature in step S4 is 450-650°C.
[0017] In some embodiments, in step S4, the temperature is increased to the sintering temperature at a rate of 5-10°C / min.
[0018] In some embodiments, in step S4, the inert atmosphere includes one of argon atmosphere, helium atmosphere, and nitrogen atmosphere.
[0019] In some embodiments, in step S1, the particle size of the metal sulfide is 5-20 nm.
[0020] In some embodiments, step S1, the preparation of the metal sulfide includes the following steps: A soluble salt of a metal is dissolved in a first organic solvent to obtain a first solution; a soluble sulfide and a stabilizer are added to a second solvent to obtain a second solution; the first solution is added dropwise to the second solution to carry out the reaction; after the reaction is completed, the solid and liquid are separated to obtain metal sulfide nanoparticles.
[0021] In some embodiments, the concentration in the first solution is 0.1-5 mol / L.
[0022] In some embodiments, the concentration of the soluble sulfide in the second solution is 0.1-5.0 mol / L.
[0023] In some embodiments, the concentration of the stabilizer in the second solution is 0.01-1 mol / L.
[0024] In some embodiments, the dropping rate of the first solution is 0.3-1.5 mL / min.
[0025] In some embodiments, the soluble sulfide includes, but is not limited to, metallic sodium sulfide, potassium sulfide, etc.
[0026] In some embodiments, the stabilizer includes sodium citrate, etc.
[0027] In some embodiments, the first solvent includes an alcohol solvent; specifically, the alcohol solvent includes, but is not limited to, at least one of anhydrous ethanol, ethylene glycol, and isopropanol.
[0028] In some embodiments, the second solvent includes an alcohol solvent; specifically, the alcohol solvent includes, but is not limited to, at least one of anhydrous ethanol, ethylene glycol, and isopropanol.
[0029] The present invention also provides a functionalized graphene-supported metal single-atom composite material obtained by the preparation method of any of the above embodiments.
[0030] This invention also provides the application of the above-mentioned functionalized graphene-supported metal single-atom composite material as an electrode active material in electrochemical energy storage devices.
[0031] Furthermore, the application of the composite material as a negative electrode active material in electrochemical energy storage devices is provided.
[0032] Furthermore, the electrochemical energy storage device includes, but is not limited to, sodium-ion batteries and sodium-ion capacitors.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: The functionalized graphene-supported metal single-atom composite material provided by this invention involves uniformly anchoring metal sulfide nanoparticles onto the surface of functionalized graphene using a specific method, and then converting them in situ into high-density, highly dispersed metal single-atom sites through low-temperature pyrolysis, significantly improving the interfacial activity and structural stability of the material. In this composite material, the functionalized graphene not only provides a highly conductive network and abundant defect anchoring sites, but its surface oxygen-containing functional groups can also effectively capture and stabilize metal single atoms, preventing their migration and aggregation during electrochemical cycling or heat treatment.
[0034] When used as an anode material for sodium-ion batteries, this composite material exhibits excellent electrochemical performance. On one hand, the metal single-atom sites serve as highly efficient active centers for sodium ion adsorption and storage, significantly improving the material's specific capacity. On the other hand, the graphene three-dimensional conductive framework effectively alleviates the volume expansion during sodium ion insertion / extraction, while simultaneously promoting rapid electron and ion transport, thus achieving high-rate performance and long-cycle stability. Experimental results show that this anode material achieves high performance at 10 A g. -1 It can achieve a reversible specific capacity of over 700 mAh / g at current density, and the capacity retention rate is over 90% after 100 cycles at 10 A / g, demonstrating its application potential in sodium-ion battery systems.
[0035] In summary, this invention achieves the efficient construction of metal single atoms on graphene, possessing both high electrochemical performance and multifunctional catalytic potential, providing a new approach for the development of next-generation sodium-ion battery anode materials and high-performance single-atom catalysts.
[0036] Furthermore, the single-atom metal structure constructed in this invention also shows great promise in the field of heterogeneous catalysis. Because the metal atoms are highly dispersed in an isolated form on the graphene surface, their coordination environment is tunable, and their d-band center positions are unique, significantly enhancing the intrinsic activity and selectivity for key catalytic processes such as the oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), and CO2 electroreduction. Simultaneously, the excellent chemical stability and conductivity of the functionalized graphene support facilitate electron transfer and intermediate desorption during catalysis, further enhancing catalytic durability. Therefore, this composite material is not only suitable for advanced energy storage devices but can also be extended to cutting-edge fields such as electrocatalysis, photocatalysis, and the degradation of environmental pollutants. Attached Figure Description
[0037] Figure 1 This is a TEM image of the antimony single-atom composite material supported on graphene oxide prepared in Example 1 of the present invention; Figure 2 The elemental distribution diagram of the antimony single-atom composite material supported on graphene oxide prepared in Example 1 is shown. Figure 3 Image of the graphene oxide sample with antimony single atoms prepared in Example 1, obtained by aberration-resolved transmission electron microscopy. Figure 4 The X-ray synchrotron radiation near-edge structure fine spectrum of the graphene oxide-supported antimony single-atom composite material prepared in Example 1; Figure 5 Thermogravimetric analysis curves and differential thermal analysis curves of the composite material obtained in Example 1 are shown. Figure 6 The graph shows the cycle performance of the composite material prepared in Example 1 as a negative electrode material in a sodium-ion battery. Detailed Implementation
[0038] Numerous specific details are set forth in the following description to provide a full understanding of the invention. However, the invention can be practiced in many other ways different from those described herein, and similar modifications can be made by those skilled in the art without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0040] Example 1 A graphene oxide-supported antimony single-atom composite material, the preparation method of which includes the following steps: S1. Preparation of functionalized graphene materials: Using fine graphite powder that has passed through a 325-mesh sieve as raw material, the optimized Hummers method is followed by the following steps: (1) Pre-oxidation process: 5g of phosphorus pentoxide and 5g of potassium persulfate are slowly added to 12mL of concentrated sulfuric acid. The addition process lasts for 10 minutes. While stirring continuously, 3g of graphite powder is slowly added. After the mixture is stirred evenly, the mixture is placed in a water bath or oil bath environment and stirred and heated. Stirred at 80℃ for 12 hours. During this process, it can be observed that the volume ratio of black graphite powder particles in the mixture gradually increases. (2) Main oxidation reaction: After cooling, 240mL of concentrated sulfuric acid (98%) is slowly added to the system, and then 30g of potassium permanganate (KMnO4) is added in batches. During the addition of potassium permanganate, the temperature is controlled below 10℃ by an ice bath. Then the temperature was raised to 35°C and the reaction was stirred for 120 min; (3) Dilution and termination of reaction: 2L of deionized water was slowly added to dilute the system and stirred for 20 min; (4) Reduction of residual oxidant: 20mL of hydrogen peroxide (H2O2, usually 30%) was added, the solution color changed from brownish-black to bright yellow, and a large amount of gas was released; (5) Purification and drying: 50mL of concentrated hydrochloric acid (HCl) was added, and then the solution was repeatedly centrifuged and redispersed with pure water until the supernatant no longer produced obvious precipitation. Then the product was put into a dialysis bag and dialyzed 5–10 times in a large amount of deionized water, the total dialysis volume was 100 times the original solution volume, until the product pH value was greater than 3 and the conductivity was less than 100μS / cm, thus obtaining the graphene oxide aqueous dispersion, and after freeze drying, graphene oxide flocculent powder was obtained; Preparation of S2, antimony sulfide (Sb2S3) nanoparticles: (1) SbCl3 was dissolved in anhydrous ethanol to obtain a 0.5 mol / L antimony chloride solution; (2) Na2S·9H2O and citric acid were added to anhydrous ethanol to obtain a mixed solution with a sodium sulfide concentration of 0.05 mol / L and a citric acid concentration of 0.05 mol / L; (3) At a stirring speed of 600 rpm, the antimony chloride solution was added dropwise to the mixed solution at a rate of 0.5 mL / min while stirring; (4) After the reaction was completed, the solid was centrifuged at 8000 rpm for 10 min, washed with ethanol and water three times alternately, and dried under vacuum at 60℃ to obtain Sb2S3 nanoparticles with a particle size of 10-20 nm. S3. Preparation of graphene / antimony sulfide nanoparticle composite material: (1) Disperse the antimony sulfide particles obtained in step S2 in deionized water at a concentration of 0.5 g / mL, and ultrasonically disperse them in an ice bath for 30 min to obtain a sulfide particle suspension; (2) Disperse the graphene oxide obtained in step S1 in an aqueous solution at a concentration of 5 mg / mL, and ultrasonically disperse it in an ice bath for 30 min to obtain a graphene suspension; (3) Mix the two suspensions at a volume ratio of 1:1 to obtain a mixed suspension; (4) Take 0.1 times the mass of the mixed suspension of bicarbonate Ammonium particles were slowly and uniformly added to the mixed suspension while stirring at a low speed (200 rpm). The addition speed was marked by the complete dissolution of ammonium bicarbonate. The particles were added in 30 minutes. During this process, it was observed that the solids in the suspension produced obvious agglomeration and obvious flocculent characteristics. (5) The mixed suspension obtained after adding ammonium bicarbonate was heated and reacted at 90°C for 240 minutes. As the gas overflowed, a black flocculent suspension was obtained. (6) After removing the supernatant, the obtained product was freeze-dried to obtain a graphene oxide-supported sulfide nanoparticle composite material. S4. Sulfide melting-pyrolysis in one step to generate metal single-atom sites: The graphene oxide-supported sulfide nanoparticle composite material is placed in a tube furnace under Ar atmosphere protection and heated to 500℃ for melting-pyrolysis reaction for 5h to obtain the graphene oxide-supported antimony single-atom composite material.
[0041] The composite material obtained in this embodiment was characterized, and the results are as follows: Figures 1-4 As shown.
[0042] in, Figure 1 TEM images of the composite material, by Figure 1 The wrinkled structure of the graphene oxide thin layer is clearly visible, but there are no distinguishable antimony sulfide structural features.
[0043] Figure 2 for Figure 1 The sampling results of energy spectrum mapping of elemental distribution under high-angle dark-field conditioning show that... Figure 1 In the typical graphene features of the field of view, carbon, sulfur, oxygen, and antimony elements can be seen to be evenly distributed.
[0044] Figure 3 This is a high-angle dark-field image of the composite material under a spherical aberration-corrected field emission electron microscope. In this mode, independent bright spots can be clearly seen distributed in the field of view, indicating that antimony is loaded in graphene oxide in the form of single atoms. Figure 4 For the fine spectrum of near-edge structure of composite materials by X-ray synchrotron radiation, from Figure 4 It can be seen that the bonding length of antimony in the sample is basically only around 1.2-1.3, which is a typical form of metal single-atom bonding, further indicating that antimony is loaded in graphene oxide in the form of single atoms.
[0045] Finally, the composite material sample was thermally decomposed to obtain its thermogravimetric curve and differential thermal analysis curve, as shown below. Figure 5 As shown. Figure 5 The thermal decomposition process of the composite material exhibits four distinct stages: linear weight loss from room temperature to 180℃ (4.09%), attributed to physically adsorbed water and solvent evaporation; a sharp drop (6.20%) with a strong exothermic peak at 200-220℃, corresponding to the oxidative decomposition of oxygen / sulfur functional groups; uniform weight loss (11.81%) at 380-500℃, mainly due to the combustion oxidation of the graphene carbon skeleton; and slow weight loss (4.96%) at 500-1000℃, after which the curve tends to be horizontal, indicating that the reaction has ended and a stable residue has been left. The cumulative total weight loss rate is 27.06%, meaning the final mass residue rate at 1000℃ is 72.94%. Based on inorganic stoichiometry, assuming the high-temperature residue is completely converted into stable antimony trioxide (Sb₂O₃), and using the theoretical mass fraction of Sb in Sb₂O₃ (approximately 83.53%), after deducting the contribution of oxygen from the residual oxide, the mass percentage of antimony (Sb) in the composite sample is approximately 60.9%. Further atomic normalization calculations based on the estimated molar ratios of carbon, sulfur, and oxygen yield an atomic percentage of approximately 16.8% for antimony (Sb). This indicates that the sample possesses an extremely high metal loading and excellent macroscopic thermal stability.
[0046] The prepared composite material was used as the active material and mixed with conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) solvent was added, and the mixture was ground uniformly to obtain a slurry. The slurry was uniformly coated onto the surface of a copper foil, vacuum dried at 60°C for 12 hours, and then punched into circular electrode sheets with a diameter of 12 mm. The active material loading was approximately 1.0-1.5 mg / cm². 2 ; Using the aforementioned electrode sheet as the working electrode, a sodium metal sheet as the counter electrode, and glass fiber (Whatman GF / D) as the separator, 1M NaClO4 dissolved in ethylene carbonate (EC) / diethyl carbonate (DEC) (volume ratio 1:1) and 5% fluoroethylene carbonate (FEC) as the electrolyte, a CR2032 coin cell was assembled in an argon glove box (H2O and O2 contents are both below 0.1 ppm); The assembled battery was subjected to constant current charge-discharge testing on a LAND CT2001A battery testing system, with a voltage window of 0.01-3.0V (vs. Na / Na+). Cyclic performance testing was then conducted at a 1C (1C=500 mA / g) current density, and the results are as follows: Figure 6 As shown.
[0047] from Figure 6It can be seen that at a current density of 10 A / g, the initial discharge specific capacity of the graphene oxide-supported antimony single-atom composite material is 720 mAh / g, the initial charge specific capacity is 650 mAh / g, and the coulombic efficiency is 90.7%. After 100 cycles, the reversible specific capacity still exceeds 600 mAh / g, and the capacity retention rate is 92%.
[0048] This indicates that the functionalized graphene-supported antimony single-atom composite material has excellent electrochemical sodium storage performance and high cycle stability, which is beneficial for its application as a high-performance anode material in sodium-ion batteries.
[0049] Example 2 A graphene oxide-supported nickel single-atom composite material, the preparation method of which includes the following steps: S1. Preparation of functionalized graphene materials: Using fine graphite powder that has passed through a 325-mesh sieve as raw material, the optimized Hummers method is followed by the following steps: (1) Pre-oxidation process: 5g of phosphorus pentoxide and 5g of potassium persulfate are slowly added to 12mL of concentrated sulfuric acid. The addition process lasts for 10min. While stirring continuously, 1g of graphite powder is slowly added. After the mixture is stirred evenly, it is placed in a water bath or oil bath environment and stirred and heated. It is stirred at 80℃ for 12 hours. During this process, the volume ratio of black graphite powder particles in the mixture can be observed to gradually increase. (2) Main oxidation reaction: After cooling, 240mL of concentrated sulfuric acid is slowly added to the system, and then 30g of potassium permanganate (KMnO4) is added in batches. During the addition of potassium permanganate, the temperature is controlled below 10℃ in an ice bath. Then the temperature is raised to 35°C and the reaction is stirred for 120min. (3) Dilution and termination of reaction: 2L of deionized water is slowly added to dilute the system and stir for 20min. (4) Reduction of residual oxidant: Add 20 mL of hydrogen peroxide (H2O2, usually 30%). The solution color changes from brownish-black to bright yellow, and a large amount of gas is released. (5) Purification and drying: Add 50 mL of concentrated hydrochloric acid (HCl), and then repeatedly centrifuge and redisperse with pure water until the supernatant no longer produces obvious precipitation. Then, put the product into a dialysis bag and dialyze it 5–10 times in a large amount of deionized water, with a total dialysis volume of 100 times the original solution volume, until the product pH value is greater than 3 and the conductivity is less than 100 μS / cm. At this point, an aqueous dispersion of graphene oxide is obtained. After freeze-drying, graphene oxide flocculent powder is obtained. S2. Preparation of graphene / nanoparticle composite structure: (1) Disperse nickel sulfide particles (commercially available) with uniform size distribution and less than 20 nm in deionized water at a concentration of 0.5 g / mL, and ultrasonically disperse in an ice bath for 30 min to obtain a sulfide particle suspension; (2) Disperse graphene oxide obtained in step S1 in an aqueous solution at a concentration of 5 mg / mL, and ultrasonically disperse in an ice bath for 30 min to obtain a graphene suspension; (3) Mix the above two suspensions uniformly at a volume ratio of 1:1 to obtain a mixed suspension; (4) Take the mixed suspension... Ammonium bicarbonate particles, with a mass of 0.1 times that of the suspension, were slowly and uniformly added while the suspension was being stirred at a low speed. The addition rate was determined by the complete dissolution of the ammonium bicarbonate. The addition was carried out over 30 minutes. During this process, it was observed that the solids in the suspension produced obvious agglomeration and flocculent characteristics. (5) The mixed suspension obtained after adding ammonium bicarbonate in step (4) was heated and reacted at 90°C for 240 minutes. As the gas overflowed, a black flocculent suspension was obtained. (6) After freeze-drying, a graphene / sulfide nanoparticle composite material was obtained. S3. Sulfide melting-pyrolysis to generate metal single-atom sites in one step: The composite material is placed in a tube furnace under Ar atmosphere protection and heated to 500℃ to carry out a melting-pyrolysis process to obtain the functionalized graphene-supported nickel single-atom composite material.
[0050] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0051] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.
Claims
1. A method for preparing a functionalized graphene-supported metal single-atom composite material, characterized in that, Includes the following steps: S1. Disperse the metal sulfide and graphene oxide evenly in water to obtain sulfide suspension and graphene oxide suspension respectively. S2. Mix the sulfide suspension and the graphene oxide suspension evenly to obtain a mixed suspension; S3. Add the weak electrolyte salt to the mixed suspension, mix evenly, and then heat to carry out the reaction. After the reaction is completed, dry the product to obtain precursor particles. S4. Place the precursor particles in a protective atmosphere or vacuum, and heat them for sintering to obtain a functionalized graphene-supported metal single-atom composite material. Wherein, the metal sulfide is antimony sulfide; The particle size of the metal sulfide is 5-20 nm; The preparation of the graphene oxide includes the following steps: (1) Pre-oxidation process: Add phosphorus pentoxide and potassium persulfate to concentrated sulfuric acid. The addition process lasts for 10 minutes. While stirring continuously, add graphite powder. After the mixture is stirred evenly, place the mixture in a water bath or oil bath environment and stir and heat it. Stir at 80°C for 12 hours. (2) Main oxidation reaction: After cooling, add 240 mL of concentrated sulfuric acid to the system, then add potassium permanganate. During the addition of potassium permanganate, the temperature is controlled below 10 °C using an ice bath; then the temperature is increased and the reaction is stirred. (3) Dilution and termination of reaction: Add deionized water to the reaction system to dilute the system, and then add hydrogen peroxide to reduce the residual oxidant; (4) Purification and drying: Add concentrated hydrochloric acid, then repeatedly centrifuge and redisperse with pure water until the supernatant no longer produces obvious precipitation; then put the product into a dialysis bag and dialyze it 5–10 times in a large amount of deionized water, with a total dialysis volume of 100 times the original solution volume, until the product pH value is greater than 3 and the conductivity is less than 100 μS / cm, to obtain an aqueous dispersion of graphene oxide, which is then freeze-dried to obtain flocculent powder of graphene oxide. In step S3, the reaction temperature is 50-90℃; In step S4, the sintering temperature is 450-500℃.
2. The method for preparing the functionalized graphene-supported metal single-atom composite material according to claim 1, characterized in that, In step S1, the concentration of the sulfide suspension is 0.05-0.5 g / mL; the concentration of the graphene oxide suspension is 0.1-20 mg / mL.
3. The method for preparing the functionalized graphene-supported metal single-atom composite material according to claim 1, characterized in that, In step S2, the volume ratio of the sulfide suspension to the graphene oxide suspension is (0.05-5):
1.
4. The method for preparing the functionalized graphene-supported metal single-atom composite material according to claim 1, characterized in that, In step S3, the weak electrolyte salt includes at least one of ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, ammonium carbonate, sodium carbonate, and potassium carbonate.
5. The method for preparing the functionalized graphene-supported metal single-atom composite material according to claim 1, characterized in that, In step S1, the preparation of the metal sulfide includes the following steps: A soluble salt of a metal is dissolved in a first organic solvent to obtain a first solution; a soluble sulfide and a stabilizer are added to a second solvent to obtain a second solution; the first solution is added dropwise to the second solution to carry out the reaction; after the reaction is completed, the solid and liquid are separated to obtain metal sulfide nanoparticles.
6. The functionalized graphene-supported metal single-atom composite material obtained by the preparation method according to any one of claims 1-5.
7. The application of the composite material of claim 6 as an electrode active material in an electrochemical energy storage device.
Citation Information
Patent Citations
Copper sulphide / graphene composite material for negative electrode of sodium-ion battery and preparation method
CN105958037A
Preparation method of grapheme-CoFeSn composite material
CN107887593A